Functional and Electrical Integration of Induced Phiripotent Stem Cell-Derived Cardiomyocytes in a Myocardial Infarction Rat Heart. Issue 12 (December 2015) - Higuchi, Takahiro; Miyagawa, Shigeru; Pearson, James T.; Fukushima, Satsuki; Saito, Atsuhiro; Tsuchimochi, Hirotsugu; Sonobe, Takashi; Fujii, Yutaka; Yagi, Naoto; Astolfo, Alberto; Shirai, Mikiyasu; Sawa, Yoshiki
In vitro expanded beating cardiac myocytes derived from induced pluripotent stem cells (iPSC-CMs) are a promising source of therapy for cardiac regeneration. Meanwhile, the cell sheet method has been shown to potentially maximize survival, functionality, and integration of the transplanted cells into the heart. It is thus hypothesized that transplanted iPSC-CMs in a cell sheet manner may contribute to functional recovery via direct mechanical effects on the myocardial infarction (MI) heart. F344/NJcl-rnu/rnu rats were left coronary artery ligated ( n = 30), followed by transplantation of Dsred-labeled iPSC-CM cell sheets of murine origin over the infarct heart surface. Effects of the treatment were assessed, including in vivo molecular/cellular evaluations using a synchrotron radiation scattering technique. Ejection fraction and activation recovery interval were significantly greater from day 3 onward after iPSC-CM transplantation compared to those after sham operation. A number of transplanted iPSC-CMs were present on the heart surface expressing cardiac myosin or connexin 43 over 2 weeks, assessed by immunoconfocal microscopy, while mitochondria in the transplanted iPSC-CMs gradually showed mature structure as assessed by electron microscopy. Of note, X-ray diffraction identified 1, 0 and 1, 1 equatorial reflections attributable to myosin and actin–myosin lattice planes typical of organized cardiac muscle fibers within the transplanted cell sheets at 4 weeks, suggesting cyclic systolic myosin mass transfer to actin filaments in the transplanted iPSC-CMs. Transplantation of iPSC-CM cell sheets into the heart yielded functional and electrical recovery with cyclic contraction of transplanted cells in the rat MI heart, indicating that this strategy may be a promising cardiac muscle replacement therapy.